Postoperative Imaging in the Throwing Athlete - Flores, Dyan V.; Huang, Brady K. (Seminars in Musculoskeletal Radiology, 2025)
Overhead throwing subjects the shoulder and elbow to substantial stresses, resulting in unique injury patterns that need to be recognized to allow appropriate treatment and return to sport. At the elbow, the ulnar collateral ligament (UCL) is the primary static restraint to valgus stress and the most commonly injured structure. UCL reconstruction is the most frequent surgical procedure in throwers and may be performed along with ulnar nerve transposition and flexor-pronator mass procedures. Posteromedial impingement and valgus extension overload syndrome are related entities that result in intra-articular pathology, such as osteophytes or bodies lodged within the olecranon fossa, also warranting excision at the time of UCL reconstruction. Shoulder injuries involve the rotator cuff (partial-thickness articular-sided tear), labrum (superior anteroposterior labral tear), and capsule (glenohumeral internal rotation deficit). Surgical options such as cuff repair, labral debridement or repair, and capsular release or tightening therefore target these structures.
Keywords: throwing; labral tear; rotator cuff tear; ulnar collateral ligament reconstruction